Performance comparison between predictive functional control and PID algorithms for an automobile cruise control system - Zainuddin, Mohamed Al-Sideque; Abdullah, Muhammad; Ahmad, Salmiah; Tofrowaih, Khairul Amri (UMP, 2022)
This work presents a performance comparison between a Predictive Functional Control (PFC) and a traditional Proportional Integral Derivative (PID) controller specifically for a cruise control application. The tuning efficacy, constraints handling, and disturbance rejection features of both controllers are analysed by comparing their closed-loop response. A simplified nonlinear vehicle longitudinal dynamics model is derived and utilised as a plant to simulate the control response from a real car. For a fair comparison, both PFC and PID are tuned to achieve the similar desired closed-loop time response. Qualitatively, the results show that PFC provides a better closed-loop response, constraints handling, and disturbance rejection compared to PID. Besides, it is also found out that the tuning approach of PFC is more intuitive and practical in nature which can be very handy for future development of an autonomous cruise control application.